The Effect of Parental Social Support on Career Decision-Making Self-Efficacy Among Madrasah Aliyah Students - Aprilia Sindy; Zainal Arifin (Institut Agama Islam Negeri Kerinci, Indonesia, 2026)
This study evaluated the impact of parental social support on Career Decision-Making Self-Efficacy (CDMSE) among 12th-grade students at MAN 1 Deli Serdang. Utilizing a quantitative causal-associative design, data were gathered from a purposively selected sample of 114 active senior high school students drawn from a target population of 199. Measurement was conducted via a 27-item Likert-scale instrument, with data subjected to validity, reliability, classical assumption, and simple linear regression analyses. Empirical results demonstrated a statistically significant positive effect of parental social support on students' career decision-making confidence ( ), yielding a regression coefficient of 0.634. The adjusted value of .341 revealed that parental support accounts for 34.1% of the variance in students' CDMSE, with the remaining 65.9% attributable to unexamined external factors. These insights underscore parental involvement—encompassing emotional support, information provision, instrumental assistance, and validation—as a key determinant in student career confidence. Consequently, the findings advocate for integrated school counseling frameworks that actively incorporate parental collaboration to enhance career guidance and decision-making readiness in madrasah settings.